Face Recognition based on Discrete Cosine Transform and Support Vector Machines - Coutinho, Gabriel Chaves Afonso; de Castro, Cristiano Leite (INFOCOMP Journal of Computer Science, 2010)
In this paper we propose a new method for face recognition using a Support Vector Machine and the Discrete Cosine Transform. Experiments were conducted with two common benchmark face databases: the Yale and the AT&T.